A Thermodynamic and Experimental Analysis of Inclusions Modification in AH36 Liquid Steel by Calcium and Magnesium Treatment - Lei Kang; Xiangwei Liao; Peng Zhang; Hui Kong; Ting Wu (Metals)
The influence of calcium and magnesium treatment under different molten steel conditions, as well as that of the alloy proportion and addition sequence of calcium and magnesium in composite treatment, on the evolution of inclusions in AH36 liquid steel was analyzed systematically based on thermodynamic calculations. The results show that the inclusions in molten steel are mainly Al2O3, which gradually transform into a liquid phase after calcium treatment with a wide range of calcium contents, indicating that calcium treatment has a significant effect on inclusion modification. Magnesium treatment mainly converts Al2O3 into MgO·Al2O3 inclusions in molten steel; however, it is not suitable to modify inclusions with magnesium treatment alone since it does not produce a significant liquid phase. The effect of calcium and magnesium composite treatment varies with the alloy content composition and the order of alloy addition. The liquid phase range of inclusions follows the order of 80%Ca + 20%Mg composite treatment > calcium treatment > 50%Ca + 50%Mg composite treatment > 20%Ca + 80%Mg composite treatment. Combining the thermodynamic and experimental analysis results, it can be concluded that the composite treatment of magnesium followed by calcium is the best. Specifically, a small amount of magnesium should be added first as the nucleating particle to promote the fine dispersion of the inclusions, thus reducing their impact on steel performance. Then, calcium should be added to modify the surface of the inclusions into a liquid phase, which can effectively reduce nozzle clogging.